Banking Company Stock Price Model - Roswinna, Winna; Lusiana Yulianti, Maria; Suharyono, Oyon; Noviana, Anna; Kusumawaardani, Astrin; Pratiwi Putri, Kartika; Pertiwi, Rd Dewi (International Journal of Advanced Multidisciplinary, 2023)
In the realm of economics, the banking sector plays a pivotal role as an intermediary between depositors and borrowers. Unique to this industry are financial ratios like the Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR). In order to explore the effects of changing economic trends on Indonesian banking companies listed on the Stock Exchange from 2011 to 2016, this study analyzes variables such as CAR, LDR, ROA, and SBI. The sample size includes 27 consecutive banking companies listed from 2011 to 2016, and the analytical tool of choice is Eviews version 8. The study utilizes Least Square Pooled analysis, preceded by Fixed Effects Model and Random Effect Model analysis. The findings of this study reveal that the stock price fluctuations can be attributed to the processing variables of CAR, LDR, ROA, and SBI, which altogether account for 21.90%. Notably, the variables of CAR and ROA have a significant impact on the stock price, while LDR and SBI have no such effect